Redox regulation of PEP activity during seedling establishment in Arabidopsis thaliana - Manuel Guinea Díaz; Tamara Hernández-Verdeja; Dmitry Kremnev; Tim Crawford; Carole Dubreuil; Åsa Strand (Nature Publishing Group, 2022)
Activation of the plastid-encoded RNA polymerase is tightly controlled and involves a network of phosphorylation and, as yet unidentified, thiol-mediated events. Here, we characterize PLASTID REDOX INSENSITIVE2, a redox-regulated protein required for full PEP-driven transcription. PRIN2 dimers can be reduced into the active monomeric form by thioredoxins through reduction of a disulfide bond. Exposure to light increases the ratio between the monomeric and dimeric forms of PRIN2. Complementation of prin2-2 with different PRIN2 protein variants demonstrates that the monomer is required for light-activated PEP-dependent transcription and that expression of the nuclear-encoded photosynthesis genes is linked to the activity of PEP. Activation of PEP during chloroplast development likely is the source of a retrograde signal that promotes nuclear LHCB expression. Thus, regulation of PRIN2 is the thiol-mediated mechanism required for full PEP activity, with PRIN2 monomerization via reduction by TRXs providing a mechanistic link between photosynthetic electron transport and activation of photosynthetic gene expression.